2011
DOI: 10.1590/s0101-60832011000500006
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubos de carbono aplicados às neurociências: perspectivas e desafios

Abstract: ResumoIntrodução: Os nanotubos de carbono (NTCs) são os nanomateriais mais promissores para aplicação terapêutica em doenças neurodegenerativas. Aplicações potenciais incluem sistemas de liberação controlada de fármacos, interfaces elétricas e substratos para crescimento celular. Objetivo: Descrever o estado da arte e as perspectivas e desafios da aplicação dos NTCs nas neurociências. Métodos: Procedeu-se a uma busca sistemática nos indexadores Medline, Lilacs e SciELO, utilizando os descritores "carbon nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
(122 reference statements)
0
2
0
3
Order By: Relevance
“…The heat treatment, which attempts to separate the synthesis products depending on their size and the chemical treatment that separates the products of the synthesis by reactivity, are both positive in the elimination of a large amount of impurities such as those generated by the catalysts (Jauris et al, 2011). Additionally, studies have demonstrated that nanotubes, when functionalized, are in a disaggregated state which results in lower toxicity, in cultured cells (Oliveira et al, 2011).…”
Section: Genotype and Compoundsmentioning
confidence: 99%
“…The heat treatment, which attempts to separate the synthesis products depending on their size and the chemical treatment that separates the products of the synthesis by reactivity, are both positive in the elimination of a large amount of impurities such as those generated by the catalysts (Jauris et al, 2011). Additionally, studies have demonstrated that nanotubes, when functionalized, are in a disaggregated state which results in lower toxicity, in cultured cells (Oliveira et al, 2011).…”
Section: Genotype and Compoundsmentioning
confidence: 99%
“…Os MWCNT são de particular interesse na medicina regenerativa por preservar as propriedades biológicas e permitirem o extenso crescimento, espalhamento e adesão de células, além de possuirem excelente biocompatibilidade celular (7) . Estudos com MWCNT demonstram que os materias contem caracteristica e propriedades que suportam o crescimento de células osteoblásticas, estimulando a produção de matriz extracelular (MEC) na formação de tecido ósseo e o crescimento de cristais de hidroxiapatita (8) .…”
Section: Introductionunclassified
“…Carbon nanotubes (CNTs) are tubular structures formed by hexagonal arrays of carbon, which can be classified into two types: single walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) [1][2][3][4] . The MWCNTs are of particular interest for regenerative medicine due to their biocompatibility that permits extensive cell adhesion, spreading, and growth.…”
Section: Introductionmentioning
confidence: 99%